Dietary Solid-state-fermentation product of Bacillus velezensis T23 alleviate hepatic steatosis, oxidative stress, gut barrier damage, and microbiota dysbiosis in juvenile genetically improved farmed tilapia (GIFT, Oreochromis niloticus) - Qiang Hao; Rolf Erik Olsen; Einar Ringø; Qianwen Ding; Tsegay Teame; Yuanyuan Yao; Chao Ran; Yalin Yang; Zhen Zhang; Zhigang Zhou (Aquaculture Reports)
The application of commensal probiotic bacteria is one of the preferable green feed additives for antibiotic substitution in aquaculture, while the application methods and detailed action mechanisms of commensal bacteria isolated from aquatic animals are not consistent with normal mammalian-derived probiotics. The purpose of this study was to evaluate the effects of solid-state fermentation product of autochthonous Bacillus velezensis T23 on improving hepatic steatosis, liver antioxidation capacity, gut injury and gut microbiota profile of genetically improved farmed tilapia (GIFT, Oreochromis niloticus). The T23 probiotic was added to the basal diet at a level of 0.00, 0.05, 0.1, 0.2 and 0.3 g/kg to develop five experimental diets, respectively. After 4 weeks of the feeding trial, the results showed that T23 supplementation notably reduced the hepatocytes vacuolization and the content of liver TAGs by downregulated the mRNA expression of the lipogenesis gene (fas), while upregulated the mRNA expression of lipid degradation genes (cpt1 and pparα) (p < 0.05). Compared with the control, the 0.3T23 group showed significantly upregulated expression levels of anti-inflammatory cytokine genes (tgf-β and il-10) in the liver of the fish (p < 0.05). Besides, the activities of antioxidase SOD and CAT were significantly upregulated in T23 treatment groups, compared with the control (p < 0.05). Fish groups fed with 0.2 g/kg and 0.3 g/kg T23 supplemented diet also exhibited significantly lower intestinal injury and intestinal inflammation via upregulating the expression of tight junction protein gene claudin, anti-inflammatory factor gene il-10 (p < 0.05). However, markedly downregulation of the mRNA level of pro-inflammatory cytokine il-1β (p < 0.05) was observed in 0.05 and 0.3T23 groups, compared with the control. 16S rRNA sequencing analysis data on gut microbiota indicated that supplementation of T23 at lower levels (0.05, 0.1 and 0.2) resulted in a remarkable elevation of the abundance of phylum Firmicutes and reduced the abundance of Proteobacteria, and the ratio of (Firmicutes +Bacteroidota +Fusobacteria) /Proteobacteria. On the contrary, feeding with 0.3T23 negatively affects the gut microbiota diversity and structure of tilapia. Therefore, a 0.2 g/kg dose is suggested to supplement the diet of Nile tilapia to improve liver health and modulate the gut microbiota profile of the fish positively. Overall, these findings provide a shred of beneficial evidence of the application of B. velezensis T23 as a green feed additive to improve the productivity and profitability of tilapia farming.